Effectiveness and safety of bivalirudin in elderly patients with coronary artery disease undergoing percutaneous coronary intervention: A real‐world study. (25th January 2022) - Li, Jing; Liu, Xiying; Ma, Sicong; Na, Kun; Qi, Zizhao; Xu, Ying; Qiu, Miaohan; Han, Yaling; Li, Yi
Abstract: Objective: To assess the effectiveness and safety of bivalirudin compared with heparin monotherapy in elderly patients undergoing percutaneous coronary intervention (PCI). Background: Bivalirudin is recommended for periprocedural use in patients undergoing PCI who are of high bleeding risk. However, its safe and efficacious use in elderly patients, a typical high bleeding risk cohort, in real world practice is yet to be reported. Methods: In this single center, real‐world observational study, 4736 consecutive elderly patients who underwent PCI were enrolled. Of these, 1240 were treated with bivalirudin and 3496 with heparin according to the periprocedural anticoagulation strategies of PCI. The primary outcome was 12‐month net adverse clinical events (NACE) defined as a composite of cardiac death, myocardial infarction, stroke, revascularization, or any bleeding. Propensity score matching (PSM) was used to balance baseline characteristics between groups. Results: After PSM, bivalirudin was found to be associated with lower rates of NACE (19.1% vs. 24.7%, p = 0.002), cardiac death (2.7% vs. 4.3%, p = 0.038), and any bleeding (10.0% vs. 12.9%, p = 0.023) compared to heparin monotherapy. No differences were found in the incidences of myocardial infarction, stroke, revascularization, stent thrombosis (0.1% vs. 0.1%, p = 1.000), and major bleedings (0.5% vs. 0.5%, p = 1.000) between the two patient groups. Conclusion: In this real‐world observational study, periprocedural use of bivalirudin in elderly patients who underwent PCI was associated with less cardiac death and any bleeding compared to heparin monotherapy, without increased risk of stent thrombosis.